2009
DOI: 10.1109/tc.2009.113
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Polynomial Expressions by Using the Extended Dual Polarity

Abstract: -A method for optimization of polynomial expressions in terms of fixed polarities for discrete functions is presented. The method is based on the principle of extended dual polarity, which provides a simple way of ordering polarities to obtain an effective way of finding the optimal polarity. The method still implies exhaustive search, but it is an optimized search, which may be expressed in very simple rules. Experimental results illustrate the effectivity of the proposed method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The better the fixed the polarity initial expression, the better the expected mixed polarity resulting expression. Finding the optimal fixed polarity expression is also in NP, but the algorithm disclosed in [13] to obtain the optimal polarity is possibly the fastest known.…”
Section: Design Based On the Reed Muller Transformmentioning
confidence: 99%
See 1 more Smart Citation
“…The better the fixed the polarity initial expression, the better the expected mixed polarity resulting expression. Finding the optimal fixed polarity expression is also in NP, but the algorithm disclosed in [13] to obtain the optimal polarity is possibly the fastest known.…”
Section: Design Based On the Reed Muller Transformmentioning
confidence: 99%
“…Using the algorithm [13] it may be found that the best polarity is obtained when all four variables are complemented, leading to the following expression, with complexity 5.…”
Section: Illustrative Casesmentioning
confidence: 99%